Factores de riesgo modificables para enfermedad cardiovascular en los estudiantes con edades de 13 a 15 años del colegio Manuel Cabrera Lozano, extensión Motupe de la ciudad de Loja. - Calderón Celi, Richard Augusto (2014)
The Cardiovascular diseases are the leading cause of death worldwide. Risk factors associated with cardiovascular disease and pathological process appears as early as childhood and adolescence, and impact on quality of life in adulthood. The objective of this research was to establish the modifiable risk factors for cardiovascular disease in teenagers between 13 and 15 years old from Loja Ecuador. The Global School Based Health Survey, Ecuador 2007 was used, including the sections, food behavior, physical activity, tobacco use. An amplified and refreshed version was used, according to the WHO last recommendations. The sample was random probability. The total sample of 120 young. A 13,33% of the teenager are at risk of overweight and 18,33% are overweight. A 5% and a 3,33% are over the 95 percentile for systolic and diastolic blood pressure respectively. Only 7,5% has healthy ingestion of fruits and vegetables, 53,2% and a 80% have high ingestion of high fat food and soda respectively. A 15% smoked a cigarette during the last month and 32,4% make sedentary activities for more than 3 hours per day. In conclusion the scholar teenagers from Loja presented high prevalence of cardiovascular risk factors, is necessary to promote strategies to help preserve actual and future health. Keywords: cardiovascular diseases, overweight, blood pressure.